Liberation Theology for a Democratic Society: Essays in Public Theology, written by Heinrich Bedford-Strohm - Cole, Jonathan (International journal of public theology, 2020)
"Liberation Theology for a Democratic Society: Essays in Public Theology, written by Heinrich Bedford-Strohm" published on 08 May 2020 by Brill.